The biochemical study of the R- and S-enantiomers of 2-(4-acetoxyphenyl)-2-chloro-Nmethylethylammonium chloride (Compound A). - Swart, Liezel Maria (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.